2012
DOI: 10.1159/000343710
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Retinal Break Formation in 23-/25-Gauge Vitrectomy versus 20-Gauge Vitrectomy

Abstract: Background: This study was undertaken to examine the possible effect of microcannula-guided entry sites on the rate of intraoperative retinal break formation. Methods: In this historical cohort study, all patients having undergone vitrectomy with epiretinal or internal limiting membrane peeling performed by one surgeon between January 2005 and March 2009 were included. All procedures with microcannula-guided entry sites (23- and 25-gauge vitrectomy) were compared to procedures without the use of microcannulas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…However, we did not find this difference comparing the 23g and 25g groups. Several papers have reported that significantly fewer peripheral retinal breaks are caused by cannulated 23g systems compared to the 20g [12,13,29]. Our entry site break rate was very low in both groups at 1 eye in each group as may have been expected since the cannulated sclerostomy system is identical in length in each gauge at 6 mm.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…However, we did not find this difference comparing the 23g and 25g groups. Several papers have reported that significantly fewer peripheral retinal breaks are caused by cannulated 23g systems compared to the 20g [12,13,29]. Our entry site break rate was very low in both groups at 1 eye in each group as may have been expected since the cannulated sclerostomy system is identical in length in each gauge at 6 mm.…”
Section: Discussionsupporting
confidence: 56%
“…A reported benefit of transconjunctival small-gauge surgery over 20g is faster visual recovery [12,13]. This study did not find that this trend continues when comparing 23g to 25g.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…16 Breaks may also be avoided via smaller microcannulas, as they may better preserve the vitreous base and prevent vitreal incarceration and dragging. 10 Twenty-five-gauge instrumentation also allows easier access to small areas, providing safer vitrectomy and more precise dissection of membranes. 12,16 Still, there remain documented concerns with the use of 25-G PPV for complicated surgical cases, including diabetic TRD.…”
Section: Discussionmentioning
confidence: 99%
“…These include reduced operative times, reduced postoperative inflammation, faster visual recovery, increased patient comfort, reduced rate of intraoperative retinal break formation, avoidance of conjunctival dissection and limbal stem cell damage, and less induced corneal astigmatism. [5][6][7][8][9][10][11][12] Upon its advent, 25-G PPV was applied towards treating macular holes, idiopathic epiretinal membranes, refractory macular edema, and non-clearing vitreous hemorrhage. 13 There were concerns that fragility or inadequate variety of instrumentation may limit its usefulness in more complicated surgical disease.…”
Section: Introductionmentioning
confidence: 99%